Formation of Accounting Policy of Enterprise — from Theory to Practice - Галюк, Л. І. (Scientific Bulletin of Ivano-Frankivsk National Technical University of Oil and Gas (Series: Economics and Management in the Oil and Gas Industry), 2015)
Points described in the article are the following: current theoretical and practical aspects of development of accounting policy, its meaning and role as an instrument of accounting process management at the enterprise and as an information source for making effective daily and strategic managerial decisions. The following analysis was performed: analysis of approaches towards understanding of concept ―accounting policy‖ in international and national normative documents, scientific resources and based on it – given reasons for separating such concepts as ―accounting policy‖ and ―accounting policy development‖ and proposed own definition of these concepts. Efficiency of usage simulating as a method for accounting policy development is argued. Because of the fact that choice is the background for accounting policy building, it is simulation combined with professional suggestion of accountant that becomes suitable scientific method which allows choosing the most appropriate model of administrative document about accounting policy, promotion of role of accounting as an informational source for making effective managerial decisions. There is a list of problematic questions raised by practical accountants in the process of accounting policy development; this list is based on the data of questionnaire evaluation of enterprises in different spheres and of different organization forms. Practical recommendations are proposed concerning solving the mentioned problematic questions; also necessity of further scientific research on the topic of development and realization of accounting policy at national enterprises is argued.